SOME GENDER ASPECTS OF SOCIALISM (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2020)
Thе article presents a brief of the results of the study of the dynamics of women's underwear at the time of socialism in Bulgaria. The choice of the research topic is inspired by the concept that the attitudes towards women, women's bodies, and women's sexuality can be revealed through the dynamics of things. Studying underwear in the context of an ideology and everyday life can help us reveal many invisible characteristics of everyday life during socialism. The author firmly believes that such a comparative study is timely and necessary to be developed in all countries of the former Soviet bloc in terms of revealing similarities and differences in ideologies, economies, and policies.
Keywords: socialism; gender; ideology; Bulgaria; underwear